Perbedaan Asupan Zat Gizi Makro Makan Pagi Pada Remaja Usia 12 - 19 Tahun Berdasarkan Tiga Daerah Dan Jenis Kelamin Di Propinsi Kalimantan Barat - Lasini, Lasini; Wiyono, Sugeng (Lembaga Penerbitan Unversitas Esa Unggul, 2012)
AbstractPhysical changes due to growth in adolescence can be affects to health and nutritional status of adolescents. It is necessary for balanced nutrition to meet the needs. The objective study was to determine differences macro nutrient intake of breakfast in adolescents aged 12-19 years based on the three areas and gender in West Kalimantan. We used secondary data Riskesdas 2010 with cross-sectional design and analytic survey. The population are all adolescents aged 12-19 years in three areas. The sample was 31 adolescents aged 12-19 years in Pontianak district, 85 in Pontianak and 32 in Singkawang. Statistical testing used independent t-test and One-way ANOVA test. The average value of z-score (nutritional status) in three regions are normal status (75%), obese (11.1%) and underweight (10.4%). The intake of Energy, carbohydrates, protein, and fat are (330.3±144.4) kcal, (53.9±20.2) g, (10.02±7.09) g and (4.9±8.72) g, respectively in the Pontianak district. In Kota Pontianak, the intake of energy, carbohydrates, protein, and fat are (305.4±172.5) kcal, (42.76±21.5) g, (9.74±8.36) g and (4.9± 8.7) g, respectively. In Singkawang the intake of energy, carbohydrates, protein, fat are (262.4±176.25) kcal, (39.08±22.2) g, (5.46±4.49) g and (8.94±12.78) g, respectively. The intake of carbohydrate and protein in breakfast time was significantly different according to three regions (p <0.05) whereas the intake of energy and fat was not significantly different (p≥0.05), and this study failed to find the differences of macro nutrient intake between men and women (p≥0.05). The government should give the information about the total of breakfast time macro nutrient intake in adolescents based on area and gender. Keywords: Macro-Nutrients intake, Breakfast, Adolescence AbstrakPerubahan fisik karena pertumbuhan pada masa remaja akan mempengaruhi status kesehatan dan gizi remaja. Untuk itu diperlukan gizi seimbang untuk memenuhi kebutuhan. Untuk mengetahui perbedaan asupan zat gizi makro makan pagi pada remaja usia 12-19 tahun berdasarkan tiga daerah dan jenis kelamin di Propinsi Kalimantan Barat. Data yang digunakan data sekunder Riskesdas 2010 dengan pendekatan cross-sectional dan design survey analitik. Populasi adalah seluruh remaja usia 12-19 tahun di tiga daerah. Sampel adalah 31 remaja usia 12-19 tahun di Kabupaten Pontianak, 85 di Kota Pontianak dan 32 di Kota Singkawang. Pengujian statistik menggunakan uji t-test Independen dan uji One-way Anova. Hasil: Nilai rata-rata z-score di ketiga daerah berstatus gizi normal (75%), status gizi gemuk (11,1%) dan kurus (10,4%). Asupan energi 330,3 kkal (±144,4), karbohidrat 53,9 gr (±20,2, protein 10,02 gr (±7,09) dan lemak 4,9 gr (±8,72) di Kabupaten Pontianak. Di Kota Pontianak asupan energi 305,4 kkal (±172,5), karbohidrat 42,76 gr (±21,5), protein 9,74 gr (±8,36) dan lemak 4,9 gr (±8,7) dan Kota Singkawang asupan energi 262,4 kkal (±176,25), karbohidrat 39,08 gr (±22,2), protein 5,46 gr (±4,49) dan lemak 8,94 gr (±12,78). Asupan karbohidrat dan protein waktu makan pagi berbeda secara bermakna berdasarkan tiga daerah (p<0,05) sedangkan asupan energi dan lemak tidak berbeda secara bermakna (p≥0,05), dan juga tidak ditemukan adanya perbedaan asupan zat gizi makro antara laki-laki dan perempuan (p≥0,05). Pemerintah perlu menginformasikan besaran asupan zat gizi makro makan pagi pada remaja terkait dengan lokasi dan jenis kelamin. Kata kunci : Asupan zat gizi makro, Sarapan, Remaja